Formative uncertainty and community perception in social engagement projects using Neutrosophic Z Numbers - Carlos Vélez; Carla Espinoza; Manuel Espinoza; Fabrizzio Andrade Zamora; Óscar José Alejo Machado (Neutrosophic Sets and Systems)
This research addresses the gap of measuring social learning of social community projects, a controversial topic stemming from the subjectivity of all involved actors. It's a relevant topic because eventually, all community projects will need to be assessed for effective educational and social gains to ensure meaningful existence for sustainability purposes. However, the literature does not provide such assessments because actions are fuzzy or blended with communities and non-deterministic learning outcomes. This research attempts to assess the measurement of social learning of social community projects using Neutrosophic Z Numbers to bring uncertainty into the measurement equation. Beginning with a proposed community learn project as a hypothetic situation, the researcher then applies neutrosophic values to the quantitative and qualitative indicators of learning and viewpoints. Findings conclude that this solution works well for assessment since it represents uncertainty better than any particular value. The contribution of this research is twofold: the new solution for assessing social projects of a community nature with empirical findings applicable to project educational developments and policy efforts and a springboard for further investigation into the realm of uncertainty within dyadic, enhanced, social realms.